Answer:
1) ![\sqrt{1225}+\sqrt{1024}=67](https://tex.z-dn.net/?f=%5Csqrt%7B1225%7D%2B%5Csqrt%7B1024%7D%3D67)
2) ![\sqrt[3]{-1331}=-11](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B-1331%7D%3D-11)
3) Evaluating
we get ![p=\pm 4](https://tex.z-dn.net/?f=p%3D%5Cpm%204)
4) ![x^3+y^2+z \ when \ x=3, y=-2, x=-6 \ we \ get \ \mathbf{25}](https://tex.z-dn.net/?f=x%5E3%2By%5E2%2Bz%20%5C%20when%20%5C%20x%3D3%2C%20y%3D-2%2C%20x%3D-6%20%5C%20we%20%5C%20get%20%5C%20%5Cmathbf%7B25%7D)
5) ![\frac{(-6)^4\times(-2)^3\times(3)^3}{(-6)^6}=-6](https://tex.z-dn.net/?f=%5Cfrac%7B%28-6%29%5E4%5Ctimes%28-2%29%5E3%5Ctimes%283%29%5E3%7D%7B%28-6%29%5E6%7D%3D-6)
Step-by-step explanation:
1) ![\sqrt{1225}+\sqrt{1024}](https://tex.z-dn.net/?f=%5Csqrt%7B1225%7D%2B%5Csqrt%7B1024%7D)
Prime factors of 1225 : 5x5x7x7
Prime factors of 1024: 2x2x2x2x2x2x2x2x2x2
![\sqrt{1225}+\sqrt{1024}\\=\sqrt{5\times5\times7\times7}+\sqrt{2\times2\times2\times2\times2\times2\times2\times2\times2\times2}\\=\sqrt{5^2\times7^2}+\sqrt{2^2\times2^2\times2^2\times2^2\times2^2}\\=5\times7+(2\times2\times2\times2\times2)\\=35+32\\=67](https://tex.z-dn.net/?f=%5Csqrt%7B1225%7D%2B%5Csqrt%7B1024%7D%5C%5C%3D%5Csqrt%7B5%5Ctimes5%5Ctimes7%5Ctimes7%7D%2B%5Csqrt%7B2%5Ctimes2%5Ctimes2%5Ctimes2%5Ctimes2%5Ctimes2%5Ctimes2%5Ctimes2%5Ctimes2%5Ctimes2%7D%5C%5C%3D%5Csqrt%7B5%5E2%5Ctimes7%5E2%7D%2B%5Csqrt%7B2%5E2%5Ctimes2%5E2%5Ctimes2%5E2%5Ctimes2%5E2%5Ctimes2%5E2%7D%5C%5C%3D5%5Ctimes7%2B%282%5Ctimes2%5Ctimes2%5Ctimes2%5Ctimes2%29%5C%5C%3D35%2B32%5C%5C%3D67)
![\sqrt{1225}+\sqrt{1024}=67](https://tex.z-dn.net/?f=%5Csqrt%7B1225%7D%2B%5Csqrt%7B1024%7D%3D67)
2) ![\sqrt[3]{-1331}](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B-1331%7D)
We know that ![\sqrt[n]{-x}=-\sqrt[n]{x} \ ( \ if \ n \ is \ odd)](https://tex.z-dn.net/?f=%5Csqrt%5Bn%5D%7B-x%7D%3D-%5Csqrt%5Bn%5D%7Bx%7D%20%5C%20%28%20%5C%20if%20%5C%20n%20%5C%20is%20%5C%20odd%29)
Applying radical rule:
![\sqrt[3]{-1331}\\=-\sqrt[3]{1331} \\=-\sqrt[3]{11\times\11\times11}\\=-\sqrt[3]{11^3} \\Using \ \sqrt[n]{x^n}=x \\=-11](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B-1331%7D%5C%5C%3D-%5Csqrt%5B3%5D%7B1331%7D%20%5C%5C%3D-%5Csqrt%5B3%5D%7B11%5Ctimes%5C11%5Ctimes11%7D%5C%5C%3D-%5Csqrt%5B3%5D%7B11%5E3%7D%20%5C%5CUsing%20%5C%20%5Csqrt%5Bn%5D%7Bx%5En%7D%3Dx%20%5C%5C%3D-11)
So, ![\sqrt[3]{-1331}=-11](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B-1331%7D%3D-11)
3) ![2:p :: p:8](https://tex.z-dn.net/?f=2%3Ap%20%3A%3A%20p%3A8)
It can be written as:
![p*p=2*8\\p^2=16\\Taking \ square \ root \ on \ both \ sides\\\sqrt{p^2}=\sqrt{16}\\p=\pm 4](https://tex.z-dn.net/?f=p%2Ap%3D2%2A8%5C%5Cp%5E2%3D16%5C%5CTaking%20%5C%20square%20%5C%20root%20%5C%20on%20%5C%20both%20%5C%20sides%5C%5C%5Csqrt%7Bp%5E2%7D%3D%5Csqrt%7B16%7D%5C%5Cp%3D%5Cpm%204)
Evaluating
we get ![p=\pm 4](https://tex.z-dn.net/?f=p%3D%5Cpm%204)
4) ![x^3+y^2+z \ when \ x=3, y=-2, x=-6](https://tex.z-dn.net/?f=x%5E3%2By%5E2%2Bz%20%5C%20when%20%5C%20x%3D3%2C%20y%3D-2%2C%20x%3D-6)
Put value of x, y and z in equation and solve:
![x^3+y^2+z \\=(3)^3+(-2)^2+(-6)\\=27+4-6\\=25](https://tex.z-dn.net/?f=x%5E3%2By%5E2%2Bz%20%5C%5C%3D%283%29%5E3%2B%28-2%29%5E2%2B%28-6%29%5C%5C%3D27%2B4-6%5C%5C%3D25)
So, ![x^3+y^2+z \ when \ x=3, y=-2, x=-6 \ we \ get \ \mathbf{25}](https://tex.z-dn.net/?f=x%5E3%2By%5E2%2Bz%20%5C%20when%20%5C%20x%3D3%2C%20y%3D-2%2C%20x%3D-6%20%5C%20we%20%5C%20get%20%5C%20%5Cmathbf%7B25%7D)
5) ![\frac{(-6)^4\times(-2)^3\times(3)^3}{(-6)^6}](https://tex.z-dn.net/?f=%5Cfrac%7B%28-6%29%5E4%5Ctimes%28-2%29%5E3%5Ctimes%283%29%5E3%7D%7B%28-6%29%5E6%7D)
We know (-a)^n = (a)^n when n is even and (-a)^n = (-a)^n when n is odd
![\frac{(-6)^4\times(-2)^3\times(3)^3}{(-6)^6}\\\\=\frac{1296\times-8\times 27}{46656}\\\\=\frac{-279936}{46656} \\\\=-6](https://tex.z-dn.net/?f=%5Cfrac%7B%28-6%29%5E4%5Ctimes%28-2%29%5E3%5Ctimes%283%29%5E3%7D%7B%28-6%29%5E6%7D%5C%5C%5C%5C%3D%5Cfrac%7B1296%5Ctimes-8%5Ctimes%2027%7D%7B46656%7D%5C%5C%5C%5C%3D%5Cfrac%7B-279936%7D%7B46656%7D%20%5C%5C%5C%5C%3D-6)
So, ![\frac{(-6)^4\times(-2)^3\times(3)^3}{(-6)^6}=-6](https://tex.z-dn.net/?f=%5Cfrac%7B%28-6%29%5E4%5Ctimes%28-2%29%5E3%5Ctimes%283%29%5E3%7D%7B%28-6%29%5E6%7D%3D-6)
Answer:
1. they both are the same length and diameter, the difference is thw diameter is a different direction.
2. 4 cm
3. EB and 8 cm
Step-by-step explanation:
Diameter is the length of the circle aross, hope this helps!
Answer:
$113.81
Step-by-step explanation:
Find the cost for one book:
35.94 / 6 = 5.99
Multiply 5.99 with the number of books buying:
5.99 x 19 = 113.81
Answer: D
Step-by-step explanation:
Answer:
![5\dfrac{7}{8} c +7](https://tex.z-dn.net/?f=5%5Cdfrac%7B7%7D%7B8%7D%20c%20%2B7)
Step-by-step explanation:
The like terms are the ones containing the variable 'c'. They are combined by adding their coefficients.
Working just with the coefficients of c, we have ...
![2\dfrac{3}{4} +3\dfrac{1}{8}=(2+3)+\left(\dfrac{6}{8}+\dfrac{1}{8}\right)=5\dfrac{7}{8}](https://tex.z-dn.net/?f=2%5Cdfrac%7B3%7D%7B4%7D%20%2B3%5Cdfrac%7B1%7D%7B8%7D%3D%282%2B3%29%2B%5Cleft%28%5Cdfrac%7B6%7D%7B8%7D%2B%5Cdfrac%7B1%7D%7B8%7D%5Cright%29%3D5%5Cdfrac%7B7%7D%7B8%7D)
Then the simplified expression is ...
(2 3/4)c +(3 1/8)c +7
= (5 7/8)c +7